2022
DOI: 10.1136/bmjopen-2021-054331
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in COVID-19 vulnerability by legal immigration status in California: a prepandemic cross-sectional study

Abstract: ObjectiveTo quantify COVID-19 vulnerabilities for Californian residents by their legal immigration status and place of residence.DesignSecondary data analysis of cross-sectional population-representative survey data.DataAll adult respondents in the restricted version of the California Health Interview Survey (2015–2020, n=128 528).Outcome measureRelative Social Vulnerability Indices for COVID-19 by legal immigration status and census region across six domains: socioeconomic vulnerability; demography and disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Cultural changes, unawareness of the new culture, and as a result, cultural-social isolation have also been considered problems faced by immigrants ( 22 , 24 , 30 ). It is useful to create communication channels between the officials and immigrants to announce their problems and participate in solving the problems ( 10 , 25 ). Some support centers should also be launched for immigrants regardless of the type of migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural changes, unawareness of the new culture, and as a result, cultural-social isolation have also been considered problems faced by immigrants ( 22 , 24 , 30 ). It is useful to create communication channels between the officials and immigrants to announce their problems and participate in solving the problems ( 10 , 25 ). Some support centers should also be launched for immigrants regardless of the type of migration.…”
Section: Resultsmentioning
confidence: 99%
“…More than half of the articles have addressed the Covid-19 epidemic and the vulnerability of immigrants and refugees ( 4 , 12 , 18 , 22 , 25 , 27 , 28 ). The most important vulnerability of this group includes livelihood problems ( 22 , 25 , 30 ) and housing and living problems ( 27 ) as well as vulnerability caused by limited access to vaccination facilities and medical care ( 20 , 22 ). Problems related to education and social isolation can also severely affect this group.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we estimated the difference in the risk of neurodevelopmental delay based on the geographical location of residence during the COVID-19 pandemic compared to before the pandemic. The geographical location of residence is an important indicator of children’s neurodevelopment, encompassing factors such as their behaviors, access to well-childcare centers, treatment of neurodevelopmental dysfunction, and the diagnosis of neurodevelopment [ 17 , 40 ]. Further, we found that the negative impacts on fine motor function, cognition, communication, social interaction, and self-care were more pronounced among urban children.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study provides two key contributions to the literature on COVID-19 vaccine health inequities by race, ethnicity, and citizenship. First, although previous studies have examined COVID-19 inequities by race and ethnicity [ 10 , 11 , 28 ] or have speculated how there may be disparities by citizenship [ 8 , 9 , 12 , 27 , 34 ], our study provides a detailed look at how willingness to vaccinate may be different by race/ethnicity and citizenship. Examining the intersections of race, ethnicity, and citizenship allows us to examine how potential vulnerability compounds to produce health inequities [ 35 ].…”
Section: Discussionmentioning
confidence: 99%